Endo-Perio Lesions and Dentists’ Treatment Approach: A Survey - DURMAZPINAR, PARLA MEVA (My University, 2024)
Background: Endo-perio lesions are a great challenge for dentists. The aim of this study was to evaluate the treatment approach of dental practitioners to endo-perio lesions by considering the current endo-perio classification. Material/Methods: An online survey was prepared, consisting of questions about the treatment approach to 3 simulated cases with endo-perio lesions, shown on periapical radiography. Details of the patient’s age, presence of systemic disease, smoking, and how the single- or multi-rooted tooth would affect the treatment plan were also included in the simulated cases presented in the survey. The survey was sent to 1500 dentists via e-mail, WhatsApp, and social media platforms. The chi-square test was used for comparison of data. Significance was evaluated at P<0.05. Results: In total, 338 dentists participated in the survey, including general dentists, endodontists, and periodontists. Fifty-three percent of participants stated that they would perform root canal treatment and initial periodontal treatment simultaneously, when both treatments were required. In cases classified as grade 3, most general dentists, endodontists, and periodontists answered that they would prescribe systemic antibiotics if there was diffuse extra-oral swelling (P<0.05). Moreover, in grade 3 cases, more general dentists chose the option \"extraction\" as the best choice, compared with endodontists and periodontists, who did not choose extraction as often (P<0.05). Conclusions: According to the results of this study, general dentists, endodontists, and periodontists generally follow different approaches to endo-perio lesions. A consensus is needed on this issue to develop a successful multidisciplinary approach to endo-perio lesions.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Clinical Protocols; Endodontics; Periodontal Diseases